Citrullination is an inflammation-dependent process. Issue 9 (15th March 2006) - Makrygiannakis, D; af Klint, E; Lundberg, I E; Löfberg, R; Ulfgren, A-K; Klareskog, L; Catrina, A I
Abstract : Objectives: To study the presence of citrullinated proteins in inflammatory conditions and in clinically non-affected tissues of controls. Methods: Synovial biopsy specimens from 19 patients with rheumatoid arthritis and 10 healthy controls were investigated by immunohistochemistry. Additionally, muscle tissue from 5 patients with polymyositis and from 7 healthy controls, intestinal tissue from macroscopically affected and non-affected areas from 10 patients with inflammatory bowel disease (IBD) and tonsil tissues from 4 chronically inflamed tonsils were studied. Results: Citrullinated proteins were present in all synovial biopsy specimens from patients with rheumatoid arthritis, whereas only three of 10 healthy synovial biopsy specimens showed scarce amounts of citrullination. Citrullination was also present in all myositis-affected muscles, whereas it was absent in the muscle tissues of controls. All tonsil biopsy specimens studied were positive for citrulline. Even though more frequently detected in the macroscopically affected colonic areas, no marked difference was observed in the pattern or extent of citrullination between the macroscopically affected and non-affected intestinal IBD tissues. Conclusion: Citrullination is present in a wide range of inflammatory tissues, suggesting that this process is inflammation dependent rather than disease dependent.